Sustainability Report Quality: Effect of Media Exposure, Stakeholder Pressure, Audit Committee - Putu Mita Cahyani; I Ketut Sujana (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
Sustainability report is denoted as the measurement and disclosure of company’s efforts as an obligation to stakeholders, encompassing the company's progress towards sustainable development objectives. The evaluation of sustainability report quality is established by the GRI Standard, the more indicators that are disclosed, the better the quality of the sustainability report. The objective of this study is to ascertain the influence of media exposure, stakeholder pressure, and audit committee on sustainability report’s quality. The study was carried out using SRI-KEHATI index firms in 2022 on IDX. The sampling approach utilized was non-probability sampling employing purposive sampling technique, so that 63 observations were obtained. Data collection using non-participant observation method, by utilizing SPSS and applying multiple linear regression analysis techniques. The test outcomes reveal that media exposure, environmental pressure, consumer pressure, and audit committee contribute positively to sustainability report’s quality. Concurrently, employee pressure does not influence sustainability report quality and shareholder pressure exerts a detrimental impact on sustainability report quality. The implications of this research support theories of stakeholder and legitimacy, and help users of sustainability report information or stakeholders, especially investors, creditors, and the public in determining the company's sustainability report quality.